Content Analysis and Teachers’ Attitudes towards the Ministerial English Diagnostic Tests Case of the Newly Recruited Teachers at Souk Ahras University - BENMAKHLOUF Ranim Zaher El Youm (My University, 2024)
Abstract This dissertation investigates the attitudes of newly recruited teachers at Souk Ahras University towards the ministerial diagnostic tests in English. The study aims to evaluate the effectiveness of these tests in measuring the English language proficiency required for academic instruction. Employing a mixed-methods approach, this research combines quantitative surveys and qualitative content analysis to provide a comprehensive understanding of teachers' perceptions and the adequacy of the diagnostic tests. The findings reveal a mixed level of satisfaction among teachers, highlighting significant concerns regarding the absence of speaking assessments, technical issues, and the relevance and clarity of test content. Based on these insights, several recommendations are proposed to enhance the design and implementation of the diagnostic tests. This study contributes to improving the assessment procedures, ensuring they effectively evaluate the specific competencies required for effective teaching and scholarly communication in a multilingual and multicultural academic context. --------------- الملخص تستقصي هذه الأطروحة مواقف الاساتذة الجدد في جامعة سوق أهراس تجاه الاختبارات التشخيصية الوزارية في اللغة الإنجليزية. تهدف الدراسة إلى تقييم فعالية هذه الاختبارات في قياس الكفاءة اللغوية المطلوبة للتدريس الأكاديمي. باستخدام نهج متعدد الأساليب، تجمع هذه الدراسة بين الاستبيانات الكمية وتحليل المحتوى النوعي لتقديم فهم شامل لتصورات الاساتذة ومدى كفاية الاختبارات التشخيصية. تكشف النتائج عن مستوى مختلط من الرضا بين الاساتذة، مما يبرز القلق الكبير بشأن غياب تقييمات مهارات التحدث، والمشكلات التقنية، وأهمية ووضوح محتوى الاختبار. بناءً على هذه الرؤى، تم اقتراح عدة توصيات لتعزيز تصميم وتنفيذ الاختبارات التشخيصية. تساهم هذه الدراسة في تحسين إجراءات التقييم، وضمان تقييمها الفعّال للمهارات المحددة المطلوبة للتدريس الفعّال والتواصل العلمي في سياق أكاديمي متعدد اللغات والثقافات. ------------------ Résumé Cette dissertation examine les attitudes des enseignants nouvellement recrutés à l'Université  de Souk Ahras à l'égard des tests de diagnostic ministériels en anglais. L'étude vise à évaluer  l'efficacité de ces tests dans la mesure de la maîtrise de l'anglais requise pour l'enseignement académique. En utilisant une approche méthodologique mixte, cette recherche combine des enquêtes quantitatives et une analyse de contenu qualitative pour fournir une compréhension complète des perceptions des enseignants et de l'adéquation des tests de diagnostic. Les résultats révèlent un niveau de satisfaction mitigé parmi les enseignants, soulignant des  préoccupations importantes concernant l'absence d'évaluations orales, les problèmes techniques, et la pertinence et la clarté du contenu des tests. Sur la base de ces insights, plusieurs recommandations sont proposées pour améliorer la conception et la mise en œuvre des tests de diagnostic. Cette étude contribue à l'amélioration des procédures d'évaluation,  garantissant qu'elles évaluent efficacement les compétences spécifiques requises pour un enseignement et une communication académique efficaces dans un contexte académique multilingue et multiculturel.